2024
DOI: 10.2147/dmso.s446318
|View full text |Cite
|
Sign up to set email alerts
|

The Active Ingredient Catalpol in Rehmannia glutinosa Reduces Blood Glucose in Diabetic Rats via the AMPK Pathway

Yang Li,
Qiang Chen,
Hong-Juan Sun
et al.

Abstract: Background: Type 2 diabetes mellitus (T2DM) poses a huge threat to population health globally, and more drugs need to be explored for treatment. In this study, we investigated the mechanism of active ingredient catalpol in Rehmannia glutinosa on reduces blood glucose in diabetic. Methods: The T2DM model was constructed by intraperitoneal injection of streptozotocin into Sprague-Dawley (SD) rats, which were randomly grouped into diabetes model group, pioglitazone group, Rehmannia glutinosa group, catalpol high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…14 Catalpol, the principal active component of Rehmanniae Radix, is a widely used herbal medicine in East Asia, 15 possesses diverse biological activities, including antioxidative, 16 antiinflammatory, 17 and anti-ischemic effects. 18 Catalpol can also reduce blood glucose 19 and attenuate ischemic stroke. 20 Previous studies have confirmed the positive impact of catalpol on osteogenesis, enhancing bone healing in critical-sized calvarial defects in rats and mitigating bone loss in ovariectomized (OVX) rat models.…”
Section: Introductionmentioning
confidence: 99%
“…14 Catalpol, the principal active component of Rehmanniae Radix, is a widely used herbal medicine in East Asia, 15 possesses diverse biological activities, including antioxidative, 16 antiinflammatory, 17 and anti-ischemic effects. 18 Catalpol can also reduce blood glucose 19 and attenuate ischemic stroke. 20 Previous studies have confirmed the positive impact of catalpol on osteogenesis, enhancing bone healing in critical-sized calvarial defects in rats and mitigating bone loss in ovariectomized (OVX) rat models.…”
Section: Introductionmentioning
confidence: 99%